REFLEKSI AJARAN BUDHISME-ZEN TERHADAP TOKOH NENEK OSANO DALAM NOVEL SAGA NO GABAI BACHAN KARYA YOSHICHI SHIMADA. - Dewi, Albentartus Sylvina (Jurnal Ilmiah Mahasiswa FIB, 2013)
Buddhism entered Japan with the process of assimilation of the teachings of Shinto and Taoism that can be called with Zen-Buddhism. The influence of Zen-Buddhism in Japan itself, is embedded in Japanese society such as taste, style, identity, social status, personality, and mentality. Therefore, Zen-Buddhism can inspire the author to create a work that can reflect and give an overview of the life of a particular era. Writing a novel with the themes of reflection of life and certain moral teachings can provide ideas to make the author of a work, which here is novel.One novel that raised the idea teaching of Zen-Buddhism is Saga No Gabai Bachan. Therefore, in this study the authors will answer the research question is the relationship between Zen-Buddhism with a moral message to be conveyed author. This study uses the approach of Zen-Buddhism. In this study Zen-Buddhism will be described through the descriptive text.The results of this study indicate that the Japanese people especially Osano  always tried to reflect on the teachings of Buddhism-Zen in daily life. Of 8 Zen-Buddhism (astangamarga), there are 5 things that reflect morality and performed by figures which right words / speech, right action, right, right living, right effort and right thinking. In this novel taught how we should always be optimistic and look to the future with a good mind, and the words were honest.The conclusion of this research is the novel Saga No Gabai Bachan illustrates the problems faced by everyone in everyday life, which in this era, more people will be easy to quickly despair in solving his problems, and it is known that the Japanese people are always trying reflect the teachings of Zen-Buddhism without having to go to a particular place of worship. Here the authors suggest that the novelSaga No Gabai Bachan can be studied in more detail by using a psychology approach so as to know the personality / character of the main character is Osano Grandma.